Real-time fieldbus communications using Profibus networks - Tovar, Eduardo (2014)
This paper provides a comprehensive study on how to use Profibus fieldbus networks to support real-time industrial communications, that is, on how to ensure the transmission of real-time messages within a maximum bound time. Profibus is base on a simplified timed token (TT) protocol, which is a well-proved solution for real-time communication systems. However, Profibus differs with respect to the TT protocol, thus preventing the application of the usual TT protocol real-time analysis. In fact, real-time solutions for networks based on the TT protocol rely on the possibility of allocating specific bandwidth for the real-time traffic. This means that a minimum amount of time is always available, at each token visit, to transmit real-time messages, transversely, with the Profibus protocol, in the worst case, only one real-time message is processed per token visit. The authors propose two approaches to guarantee the real-time behavior of the Profibus protocol: (1) an unconstrained low-priority traffic profile; and (2) a constrained low-priority traffic profile. The proposed analysis shows that the first profile is a suitable approach for more responsive systems (tighter deadlines), while the second allows for increased nonreal-time traffic throughput